The 1st International Electronic Conference on Pharmaceutics 2020
DOI: 10.3390/iecp2020-08649
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone-Based Organic Salts and Ionic Liquids as Highly Bioavailable Broad-Spectrum Antimicrobials

Abstract: The majority of antibiotics display low oral bioavailability due to reduced solubility in water and/or inefficient permeability across biological membranes. Their efficiency is further limited by the frequent presence of polymorphic structures with different pharmaceutical activities. In this communication, we present our latest results on the development of organic salts and ionic liquids from fluoroquinolones (FQ-OSILs) as highly efficient ionic formulations of this family of antimicrobials. Ciprofloxacin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…When an API-IL is prepared, the first important question is whether the API-IL retains (or even improves) its biological activity. This has been studied in vitro on numerous API-ILs with antibacterial ions in their structure. ,,, For example, when the acidic antibiotic ampicillin was paired with hexadecyl­pyridinium, the API-IL was significantly more active against both Gram-positive and Gram-negative bacteria, compared to the parent compounds, sodium ampicillinate or hexadecylpyridinium chloride . The same API-IL exhibited higher antitumor activity than sodium ampicillinate .…”
Section: Assessment Of Pharmaceutical Activity (In Vivo and In Vitro)mentioning
confidence: 99%
See 1 more Smart Citation
“…When an API-IL is prepared, the first important question is whether the API-IL retains (or even improves) its biological activity. This has been studied in vitro on numerous API-ILs with antibacterial ions in their structure. ,,, For example, when the acidic antibiotic ampicillin was paired with hexadecyl­pyridinium, the API-IL was significantly more active against both Gram-positive and Gram-negative bacteria, compared to the parent compounds, sodium ampicillinate or hexadecylpyridinium chloride . The same API-IL exhibited higher antitumor activity than sodium ampicillinate .…”
Section: Assessment Of Pharmaceutical Activity (In Vivo and In Vitro)mentioning
confidence: 99%
“…It is important to note, however, that the prepared antibacterial compounds, have been named “Organic Salts and Ionic Liquids” (“OSILs”) and even “Organic salts” with the term “ionic liquids” listed as a keyword in a few literature examples, in order to also include high­(er) melting organic salts. We would like to warn the reader against this practice because (1) high­(er) melting organic salts have their own designation in the field as “a group of uniform materials based on organic salts” (GUMBOS), (2) it is the intentional development of liquid forms of APIs with targeted melting points below body temperature that allows for elimination of a growing number of problems associated with solid dosage forms of pharmaceuticals, and (3) listing “ionic liquids” as a keyword for a research paper that only deals with higher-melting solids results in erroneous databases searches.…”
Section: Assessment Of Pharmaceutical Activity (In Vivo and In Vitro)mentioning
confidence: 99%
“…Our goal is to address the limitations of NORF in terms of solubility, hydration stability, and diffusion permeability through crystal engineering. Numerous reports are available on NORF solid forms such as cocrystals, salts, polymorphs, hydrates, and eutectics to improve its physicochemical properties. NORF forms metal complexes with Cu, Tb, Ni, Ti, Cr, Mn, Fe, Ba, V, Zn, Cd, Mg, Ag, W, Co, Pd, and Bi. NORF cocrystals have been reported with isonicotinamide and salt-cocrystals with saccharin, terephthalic acid, and hexadienoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this study is important because it offers a comparison of crystal structures and physicochemical behavior between the anhydrous and hydrated forms of NORF cocrystals and salts. A limitation of several of the cocrystal/salt reports, including recent ones, is that they typically deal with one or two coformers, thus making it difficult to draw broad conclusions across a spectrum of salts/cocrystals of NORF in terms of structure–property and hydrate–anhydrate correlations due to limited data. The present report fills this gap for future crystal engineering of high bioavailability pharmaceutical cocrystals …”
Section: Introductionmentioning
confidence: 99%
“…The conversion of a bioactive compound or an active pharmaceutical ingredient (API) into an API-OSIL allows the fine-tuning of their physicochemical and pharmacological properties, leading to the development of substances with improved water solubility, membrane permeability, bioavailability, and biological activity. Particularly, with regard to the development of antibiotics, our group has recently studied the properties of fluoroquinolone (ciprofloxacin and norfloxacin) [51][52][53] and β-lactam (penicillin G and amoxicillin hydrolysates, and ampicillin) [54,55] API-OSILs and their biological activities against susceptible and resistant bacteria strains. We demonstrated that properties such as water solubility and the octanol-water partition coefficient could be significantly modulated according to the choice of counter-ions.…”
Section: Introductionmentioning
confidence: 99%